2022
DOI: 10.3847/1538-4357/ac4d8c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Imprints of Eruptive and Noneruptive Solar Flares as Observed by Solar Dynamics Observatory

Abstract: The abrupt and permanent changes of the photospheric magnetic field in the localized regions of active regions during solar flares, called magnetic imprints (MIs), have been observed for nearly the past three decades. The well-known coronal implosion model is assumed to explain such flare-associated changes but the complete physical understanding is still missing and debatable. In this study, we made a systematic analysis of flare-related changes of the photospheric magnetic field during 21 flares (14 eruptive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Next, we create difference maps of the horizontal magnetic field and vertical Lorentz force estimated at the above-mentioned time frames separately. We use information on both the horizontal magnetic field (B h ) and vertical Lorentz force (F z ) independently to avoid any selection bias in identifying the areas where the most significant changes occurred as discussed in Petrie (2012), Liu et al (2022), Vasantharaju et al (2022), and Yadav & Kazachenko (2023. To these difference maps we apply a threshold to select the subregions that demarcate the area of positive change (>100 G) in the horizontal magnetic field or negative change (<-10 19 dyn) in the vertical component of the Lorentz force.…”
Section: Lorentz Force and Masking Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we create difference maps of the horizontal magnetic field and vertical Lorentz force estimated at the above-mentioned time frames separately. We use information on both the horizontal magnetic field (B h ) and vertical Lorentz force (F z ) independently to avoid any selection bias in identifying the areas where the most significant changes occurred as discussed in Petrie (2012), Liu et al (2022), Vasantharaju et al (2022), and Yadav & Kazachenko (2023. To these difference maps we apply a threshold to select the subregions that demarcate the area of positive change (>100 G) in the horizontal magnetic field or negative change (<-10 19 dyn) in the vertical component of the Lorentz force.…”
Section: Lorentz Force and Masking Algorithmmentioning
confidence: 99%
“…Extending the study to large recurrent flares, Sarkar et al (2019) found that the change in net vertical Lorentz force acts as an excellent proxy to predict recurrent large flaring events from a single AR. Vasantharaju et al (2022) reported that the changes in vertical Lorentz force during flares near PILs correlate well with the flare strength. However, no clear classification of the association of flares with CMEs has been made to statistically distinguish them by the net change in Lorentz force.…”
Section: Introductionmentioning
confidence: 95%
“…Wang et al (1994) showed impulsive magnetic shear enhancements along the flaring neutral line during six X-class flares, and Wang et al (2012) observed the rapid enhancement of magnetic shear in the localized region of the PIL during an X2.2 flare that occurred in NOAA 11158. This is mostly caused by the changes in the photospheric magnetic fields, especially the enhancement of horizontal magnetic fields near the PIL region (Wang et al 2012;Zuccarello et al 2020;Vasantharaju et al 2022), as a consequence of coronal implosion during flares (Hudson et al 2008). However, the result could be different if the analysis is extended from localized regions of the PIL to the whole flaring area.…”
Section: Magnetic Nonpotentiality and Confinednessmentioning
confidence: 99%